The role of wireless sensor networks in the modern landscape: a concise examination - Salwa El-Morsy (Big Data and Computing Visions)
Wireless sensor networks are fast process of connection in part such as agriculture, healthcare, environmental monitoring, security, and manufacturing and also it thesaurus and measure physical signals and it also have wireless communication. Wireless sensors also can track the appliances; it is an automatic control of devices. It works as an investigation of types and application of wireless sensors in the ground and home. In this paper we have presented sort study on WSN applications.